Clinical Outcomes of Drug-Eluting Bead Transarterial Chemoembolization Loaded with Raltitrexed for the Treatment of Unresectable or Recurrent Hepatocellular Carcinoma. (23rd August 2022) - Bi, Yonghua; Jiao, Dechao; Ren, Jianzhuang; Han, Xinwei
Abstract : Objectives . Although raltitrexed shows therapeutic effects in many types of malignant tumors, the therapeutic effects and safety of drug-eluting bead transarterial chemoembolization (DEB-TACE) loaded with raltitrexed for the treatment of hepatocellular carcinoma (HCC) are rare. This study aimed to investigate the safety and efficacy of DEB-TACE with raltitrexed-loaded CalliSpheres beads (CB) in patients with unresectable or recurrent HCC. Methods . Between May 2018 and October 2021, 41 patients with unresectable or recurrent HCC treated by DEB-TACE loaded with raltitrexed were retrospectively enrolled. The primary end points were overall survival and progression-free survival. The response evaluation criteria in solid tumors (RECIST) criteria and modified RECIST criteria (mRECIST) were used to assess the tumor response after the DEB-TACE procedure. Results . A total of 79 DEB-TACE procedures were successfully performed, and the technical success rate was 100%. The overall response rate and disease control rate assessed by mRECIST criteria were 76.9% and 88.5%, 62.5% and 70.8%, and 35.3% and 47.1%, respectively, at 1, 3, and 6 months postprocedure. The mean progression-free survival and overall survival were 21.6 ± 3.6 and 43.7 ± 5.8 months, respectively. The 6-, 24-, and 36-month overall survival rates were 86.8%, 62.7%, and 57.1%, respectively. Minor complications were observed in 21 patients (51.2%), with no treatment-related mortality or severe adverse events. The most common treatment-related complications were abdominal pain (48.8%) and nausea (29.3%). Conclusion . DEB-TACE with raltitrexed-loaded CB suggests a feasible, safe, and efficacious palliative regimen in unresectable or recurrent HCC patients.